2022
DOI: 10.21203/rs.3.rs-1315661/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cytotoxic T cells specific for alpha-myosin drive immunotherapy related myocarditis

Abstract: Immune-related adverse events, particularly severe toxicities such as myocarditis, are major challenges to immune checkpoint inhibitor (ICI) utility in anti-cancer therapy1. The pathogenesis of ICI-myocarditis is poorly understood. Pdcd1-/-Ctla4+/- mice recapitulate clinicopathologic features of ICI-myocarditis, including myocardial T cell infiltration2. Single cell RNA/T cell receptor (TCR) sequencing on the cardiac immune infiltrate of Pdcd1-/-Ctla4+/- mice identified activated, clonal CD8+ T cells as the do… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Recently, a preprint article highlights the importance of CD8 + T cells in a genetic murine model (Pdcd1−/−Ctla4+/−) that recapitulates clinicopathologic characteristics of ICI-myocarditis. They identified the alpha-myosin as a cardiac-specific antigen; peptides from this protein induce the expansion of peripheral blood T cells from two patients with ICI-myocarditis indicating its clinical importance ( Balko et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a preprint article highlights the importance of CD8 + T cells in a genetic murine model (Pdcd1−/−Ctla4+/−) that recapitulates clinicopathologic characteristics of ICI-myocarditis. They identified the alpha-myosin as a cardiac-specific antigen; peptides from this protein induce the expansion of peripheral blood T cells from two patients with ICI-myocarditis indicating its clinical importance ( Balko et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another candidate for autoimmunity is alpha-myosin, a cardiac specific protein. A study in preprint on the pathogenesis of ICI-mediated myocarditis found that highly clonal TCRs from three independent murine cardiac TCR repertoires were able to recognize alpha-myosin epitopes ( Balko et al, 2022 ). Concordantly, alpha-myosin expanded T cells from the peripheral blood of two ICI-mediated myocarditis patients shared TCR clonotypes with diseased heart muscle, suggesting alpha-myosin to potentially be a clinically important autoantigen in ICI-mediated myocarditis.…”
Section: Cardiac Immune Checkpointsmentioning
confidence: 99%
“…Alpha myosin (MYH6, also known as MYHCA) was recently shown to be of relevance for patients with ICI myocarditis. 5 This may pave the way to more refined, antigen-specific T-cell solutions, such as engineered myosin-specific immunosuppressive chimeric antigen receptor-regulatory T cells, which could protect the heart while enabling other T cells to attack the tumor.…”
Section: Article See P 316mentioning
confidence: 99%
“…Supporting this, mouse model work has demonstrated that the disease is dependent on the presence of CD8 + T cells. 4,5 In addition, the expression of PD-L1 on myocardial tissue 1,4,6 suggests that the PD-1/PDL-1 axis may have a tolerance-promoting role in the heart, disrupted by ICI. Last, the finding of PD-1 expression on a cardiac cell subset likely to include peripheral regulatory T cells 3 may also provide an additional means through which anti–PD-1 could break immune tolerance in the heart.…”
mentioning
confidence: 99%